2015
DOI: 10.1071/mf13209
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns in the distribution of large bivalves in a permanently open temperate estuary: implications for management

Abstract: To inform management, baseline ecological studies in estuaries must be implemented at spatial scales that accommodate both environmental gradients and likely anthropogenic pressures. We describe fine-scale spatial patterns in the abundances and size structure of large infaunal bivalves inhabiting shallow sand habitats in the lower reaches of a relatively undisturbed, permanently open, temperate estuary. Sampling over 3 years at 19 sites during the autumn, when freshwater influence was minimal, revealed that So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…constricta mainly occur in creeks possess thicker soft top sediment. Previous studies also indicated that the distribution of benthic species was associated with tidal exposure time and sediment size, both of which might affect food availability to the benthos [ 46 49 ]. For instance, Sousa et al (2008) indicated that the bivalve Pisidium amnicum distribution was related with different sediment characteristics and tidal influence [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…constricta mainly occur in creeks possess thicker soft top sediment. Previous studies also indicated that the distribution of benthic species was associated with tidal exposure time and sediment size, both of which might affect food availability to the benthos [ 46 49 ]. For instance, Sousa et al (2008) indicated that the bivalve Pisidium amnicum distribution was related with different sediment characteristics and tidal influence [ 50 ].…”
Section: Discussionmentioning
confidence: 99%